Beef production from three tropical grasses in South-Eastern Queensland - Whiteman, P.C.; Ridzwan Halim, N.; Norton, B.W.; Hales, J.W. (CSIRO Publishing, 1985)
A grazing trial with beef cattle was conducted on three grasses, Paspalum plicatulum cv. Rodd’s Bay, Brachiaria decumbens cv. Basilisk (signal grass) and Panicum maximum cv. Hamil, in the first year. P. maximum was replaced by Digitaria decumbens (pangola grass) in the second and third years. There were three stocking rates (3.0, 3.75, and 5.0 steers/ha), plots were fertilized with 300 kg N/ha, in two replicates. Animal liveweight gain was low; maximum values were 650 kg/ha for pangola grass, 640 kg/ha for signal grass and 400 kg/ha for P. plicatulum. Liveweight gain was only poorly correlated with rainfall, because low winter temperatures retarded pasture growth. Correlations between liveweight gain and individual green leaf percentage in each species were high, particularly for P. plicatulum, which had only 2% green leaf in winter. Weight loss on plicatulum was therefore high in winter, and overall performance poor, even though this species had the highest percentage of green leaf in summer. Signal grass showed a higher tolerance to grazing at 5.0 steers/ha than the other grasses. Over most of the year, except in winter when only small amounts of green leaves were available, plicatulum had the lowest phosphorus percentage, sometimes below the 0.12% suggested as the critical dietary phosphorus percentage for cattle. Over all grasses, nitrogen and phosphorus concentrations were linearly related (r = 0.98). From this experiment, P. plicatulum was shown to be a poor grass for beef production and, for this grass and the other two species at this site, beef production using 300 N kg/ha could not be financially viable.